2006
DOI: 10.1007/s00234-006-0083-2
|View full text |Cite
|
Sign up to set email alerts
|

The intersubject and intrasubject reproducibility of FMRI activation during three encoding tasks: implications for clinical applications

Abstract: The goal of the present study was to evaluate the inter- and intrasubject reproducibility of FMRI activation for three memory encoding tasks previously used in the context of presurgical functional mapping. The primary region of interest (ROI) was the medial temporal lobe (MTL). Comparative ROIs included the inferior frontal and fusiform gyri which are less affected by susceptibility-induced signal losses than the MTL regions. Eighteen subjects were scanned using three memory encoding paradigms: word-pair, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 61 publications
4
28
0
Order By: Relevance
“…The cluster that we found in the LOC may reflect this attention effect. The high concurrence in this area is also in line with multiple studies (e.g., Harrington et al, 2006;Peelen and Downing, 2005) that showed a relatively high (compared to other brain regions) within-and between-subjects reproducibility of activation in the fusiform gyrus and other visual areas.…”
Section: Lateral Occipital Complex (Loc)supporting
confidence: 77%
“…The cluster that we found in the LOC may reflect this attention effect. The high concurrence in this area is also in line with multiple studies (e.g., Harrington et al, 2006;Peelen and Downing, 2005) that showed a relatively high (compared to other brain regions) within-and between-subjects reproducibility of activation in the fusiform gyrus and other visual areas.…”
Section: Lateral Occipital Complex (Loc)supporting
confidence: 77%
“…Those that rely on encoding of complex novel visual information, such as scenes, in comparison with baseline repeated images are strong activators of MTL, including posterior regions such as the parahippocampal gyrus. [16][17][18] Tasks that involve relational processing (eg, pairs of elements such as word-word or word-face; item-context associations) typically engage this region to a greater extent than those focusing on single elements, at both encoding and retrieval. [19][20][21][22][23][24] Finally, very robust activation of the MTL bilaterally is typically observed when individuals retrieve memories of events from their own personal past (ie, details of autobiographical memories) in comparison with other forms of semantic retrieval (typically word meaning but also facts about one's life).…”
Section: Memory In Temporal Lobe Epilepsy: Activation Tasks and Corrementioning
confidence: 99%
“…Reproducibility was determined in terms of the 95% confidence interval (CI) on location, or distance, as proposed by Bland and Altman (14) (Eqs. [3] and [4]). For digit location, the results of digit 2 and digit 4 were combined.…”
Section: Calculation Of Reproducibilitymentioning
confidence: 99%
“…This is particularly important when using fMRI in multisession longitudinal studies or multi-site protocols; approaches that are becoming increasingly popular for both basic and clinical research, for example when monitoring cortical recovery following an event such as a stroke (2). Studies using presurgical paradigms (3,4) have been used to explore the level of reproducibility of fMRI localization; however, findings were often constrained by the paradigm design or the use of patients. Studies in healthy subjects have determined reproducibility within visual (5), motor (6), and somatosensory (7) cortices and have explored aspects such as voxel size and spatial smoothing (7) and thresholding (6).…”
mentioning
confidence: 99%